Brønsted-acid sites promoted degradation of phthalate esters over MnO2: Mineralization enhancement and aquatic toxicity assessment. (March 2022) - Zhang, Liping; Bi, Xiuru; Wang, Zuo; Ertürk, Ali Serol; Elmaci, Gökhan; Zhao, Haiyu; Zhao, Peiqing; Meng, Xu
Abstract: Advanced oxidation processes (AOPs) are important technologies for aqueous organics removal. Despite organic pollutants can be degraded via AOPs generally, high mineralization of them is hard to achieve. Herein, we synthesized a manganese oxide nanomaterial (H2-OMS-2) with abundant Brønsted-acid sites via ion-exchange of cryptomelane-type MnO2 (OMS-2), and tested its catalytic performance for the degradation of phthalate esters via peroxymonosulfate (PMS) activation. About 99% of dimethyl phthalate (DMP) at a concentration of 20 mg/L could be degraded within 90 min and 82% of it could be mineralized within 180 min over 0.6 g/L of catalyst and 1.8 g/L of PMS. The catalyst could activate PMS to generate SO4 − ˙ and · OH as the dominant reactive oxygen species to reach complete degradation of DMP. Especially, the higher TOC removal rate was obtained due to the rich Brønsted-acid sites and surface oxygen vacancies on the catalyst. Kinetics and mechanism study showed that Mn II /Mn III might work as the active sites during the catalytic process with a lower reaction energy barrier of 55.61 kJ/mol. Furthermore, the catalyst could be reused for many times through the regeneration of the catalytic ability. The degradation and TOC removal efficiencies were still above 98% and 65% after seven consecutive cycles, respectively. Finally, H2-OMS-2-catalyzed AOPs significantly reduced the organismal developmental toxicity of the DMP wastewater through the investigation of zebrafish model system. The present work, for the first time, provides an idea for promoting the oxidative degradation and mineralization efficiencies of aqueous organic pollutants by surface acid-modification on the catalysts. Graphical abstract: Image 1 Highlights: Brønsted-acid sites of the catalyst are beneficial for enhancement of TOC removal rate. Phthalate esters were completely degraded by ion-exchanged MnO2 /PMS system. The radical mechanism was mainly involved in the degradation. Aquatic toxicity of wastewater was significantly reduced after the treatment.